Implementasi Gerakan Literasi Sekolah (GLS) SDN Sungai Andai 4 Banjarmasin - Rabiatul Azwa, Siti Nadella; Agustina, Lili; Noormaliah (UNIB Press, 2025)
The problem in this research is that students are not yet fluent in reading, and do not know letters and numbers. This research aims to find out (1) the implementation of the school literacy movement, (2) what are the supporting and inhibiting factors in the implementation of the School Literacy Movement (GLS) at SDN Sungai Andai 4 Banjarmasin. The type of research in this research is qualitative research using a qualitative narrative approach. The subjects of this research were the principal, homeroom teacher for classes 1D, 2A, and 3C at SDN Sungai Andai 4 Banjarmasin. Data collection techniques use observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The conclusions drawn in this research are (1) the implementation of GLS activities is carried out through 3 stages, namely a) the habituation stage, b) the development stage, and c) the learning stage , the school also carries out programs to support this activity, namely extracurricular speeches, creative Fridays, regular visits to the library, (2) supporting factors, complete facilities and infrastructure, various reading materials, full support parents, appropriate time allocation, and teachers' enthusiasm for learning, while the inhibiting factors are literacy habits not being a priority, lack of reading material, unsupportive environment, activities requiring good focus.